CONSTRUCTION COMPETENCCONSTRUCTION COMPETENCY OF ISLAMIC RELIGIOUS EDUCATION IN THE HIGH SCHOOL OF ISLAMIC RELIGION AL-AMANAH JENEPONTO - Mustafa, Musram; Ondeng, Syarifuddin; Siraj, Arifuddin; Yaumi, Muhammad (Jurnal Diskursus Islam, 2019)
This paper will elaborate on how the construction of Islamic Religious Education curriculum competencies at STAI Al-Amanah Jeneponto. This research is a qualitative research. The subject of this research is focused on the construction of the Islamic Religious Education curriculum at STAI Al-Amanah Jeneponto. The approach used in this research is sociological and pedagogical approach. The results showed that Islamic Religious Education curriculum construction at STAI Al-Amanah Jeneponto which is more focused on the design of the subject centered design curriculum, which is a curriculum designed to focus on Islamic Religious Education courses that are supported. The integration model found based on informant data is the "Integration Curriculum Model (ICM)" which is then developed in an integrated manner with an interdisciplinary approach to complement one another, especially those included in the Islamic Religious Education subject group.